Development of Rotary Fatigue Test Equipment Based on the Joseph Marin Approach - Prasetyo, Anang; Afrizal, Efi; Nazaruddin, Nazaruddin (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
This paper proposed the development of rotary fatigue test equipment. This equipment was used to test the JIS S45C steel, validated using the Joseph Marin approach. Analyzing the fatigue strength of JIS S45C steel using the Joseph Marin approach was compared to experimental testing. The dimension of the test specimens was based on the ASTM E 466. The test data was displayed in the form of an S-N curve. The test results showed the fatigue strength of JIS S45C steel on the whole that was close to each other, experimentally and using the Joseph Marin approach. In the infinite life region, it is known that the fatigue strength based on the Joseph Marin approach was lower than experimental tests. Therefore, if JIS S45C steel had received a hefty load repeatedly, it would fail more quickly.